2010
DOI: 10.3109/02713683.2010.513796
|View full text |Cite
|
Sign up to set email alerts
|

Comparativein VivoConfocal Microscopical Study of the Cornea Anatomy of Different Laboratory Animals

Abstract: The present study will help researchers consider appropriate models for animal experiments, depending on focus of investigation. In vivo CLSM can be used for the characterization of the living cornea over time, thus, reducing the number of animal experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 39 publications
5
66
1
2
Order By: Relevance
“…This could be a reason why there has not been good agreement in the outcome of morphometry studies. For example, in earlier studies, the cells visible by SEM on the ex vivo corneal epithelium have been reported to have a size (dimension) between 40 and 50 mm, 24 20 and 75 mm, 25 or 3 and 35 mm. 26 In contrast, in vivo specular microscopy imaging was reported to yield cell dimension values between 12 and 66 mm, 14 whereas in vivo confocal imaging was reported to indicate that most superficial cells were between 40 and 50 mm.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This could be a reason why there has not been good agreement in the outcome of morphometry studies. For example, in earlier studies, the cells visible by SEM on the ex vivo corneal epithelium have been reported to have a size (dimension) between 40 and 50 mm, 24 20 and 75 mm, 25 or 3 and 35 mm. 26 In contrast, in vivo specular microscopy imaging was reported to yield cell dimension values between 12 and 66 mm, 14 whereas in vivo confocal imaging was reported to indicate that most superficial cells were between 40 and 50 mm.…”
Section: Discussionmentioning
confidence: 95%
“…In confocal microscopy, however, a fairly large proportion of the cells (which are usually larger and have brighter reflexes) do appear to be lying on top of a background of less reflective cells that are less well resolved in detail and have medium or darker reflectivity. 8,[15][16][17][18][19][20][21][22][23] Stated another way, some cells can be seen to be in a slightly different plane as the first cells that are visualized, that is, very slightly raised above other cells, indicating that these cells are lying right on top of the epithelial surface. The IC sampling also indicates the same because, by default, the nonoverlapping cells in a monolayer have to be right at the epithelial surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the corneal cell boundary is not distinct; the cell nucleus cannot be observed, and it is more difficult to obtain a clear picture of the three-dimensional (3D) structure of the cornea, as well as cell-cell interaction. 9,12 Real-time acquisition of structural information on the cornea, with no intervention and destruction, would be crucial for investigating and diagnosing all corneal pathologies. On the basis of recent advances in optics and laser technology, several optical section techniques, such as two-photon (2PH) microscopy, have provided alternative methods for probing the cornea without the need to section and process tissue.…”
mentioning
confidence: 99%
“…using the sequence scanning mode, which allowed images to be repeatedly acquired at different focus positions, enabling the construction of a three-dimensional image. [9][10][11] The scanned images were recorded for analysis.…”
Section: Detection Of Corneal Foreign Bodies In Micementioning
confidence: 99%